MicroRNA profiling of a CD133(+) spheroid-forming subpopulation of the OVCAR3 human ovarian cancer cell line - Nam, Eun Ji (BioMed Central, 2012)
BACKGROUND: Cancer stem cells (CSCs) are thought to be a source of tumor recurrence due to their stem cell-like properties. MicroRNAs (miRNAs) regulate both normal stem cells and CSCs, and dysregulation of miRNAs has an important role in tumorigenesis. Cluster of differentiation (CD) 133(+) and spheroid formation have been reported to be one of the main features of ovarian CSCs. Therefore, we determined the miRNA expression profile of a CD133(+) spheroid-forming subpopulation of the OVCAR3 human ovarian cancer cell line. METHODS: Initially, we confirmed the enrichment of the OVCAR3 CD133 subpopulation by evaluating in vitro anchorage-independent growth. After obtaining a subpopulation of CD133(+) OVCAR3 cells with > 98% purity via cell sorting, miRNA microarray and real-time reverse transcription-polymerase chain reaction (RT-PCR) were performed to evaluate its miRNA profile. RESULTS: We found 37 differentially expressed miRNAs in the CD133(+) spheroid-forming subpopulation of OVCAR3 cells, 34 of which were significantly up-regulated, including miR-205, miR-146a, miR-200a, miR-200b, and miR-3, and 3 of which were significantly down-regulated, including miR-1202 and miR-1181. CONCLUSIONS: Our results indicate that dysregulation of miRNA may play a role in the stem cell-like properties of ovarian CSCs.